1970
DOI: 10.5424/sjar/201008s2-1353
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years using reclaimed water to irrigate a golf course in Gran Canaria

Abstract: Low focus in water management and short time data availability are the main limiting factors for reclaimed water project analysis. One of the oldest Spanish golf courses with a medium period of available data was selected to study and describe the medium time effects (25 years) on soil and aquifer as a consequence of reclaimed water reuse, and to compare the experimental results with reclaimed water quality criteria under a sustainability point of view. An excess of reclaimed water (83%) is used for this golf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The existence of water oozes under the lower and thicker soil layer and a water gallery in the slope of the Caldera in fractured ignimbrite under the pyroclastic layer corroborates the results [6]. [19]. Moreover, in this study, its narrow thickness seems not to modify the global average of electrical resistivity values as we use 20 m for the resistivity assessment presented in Figure 7.…”
Section: Volcanic Formation Horizontal Hydraulic Conductivity (M/d) K (M/d) Obtained In This Studysupporting
confidence: 88%
See 3 more Smart Citations
“…The existence of water oozes under the lower and thicker soil layer and a water gallery in the slope of the Caldera in fractured ignimbrite under the pyroclastic layer corroborates the results [6]. [19]. Moreover, in this study, its narrow thickness seems not to modify the global average of electrical resistivity values as we use 20 m for the resistivity assessment presented in Figure 7.…”
Section: Volcanic Formation Horizontal Hydraulic Conductivity (M/d) K (M/d) Obtained In This Studysupporting
confidence: 88%
“…Transported soil was measured in P5, P6, P8, P14, P15 and P16 (Figure 7). Those soils present variable hydraulic properties due to their structure and content in organic matter and will probably be less deep which explains the need to add transported soil [19]. Moreover, in this study, its narrow thickness seems not to modify the global average of electrical resistivity values as we use 20 m for the resistivity assessment presented in Figure 7.…”
Section: Volcanic Formation Horizontal Hydraulic Conductivity (M/d) K (M/d) Obtained In This Studymentioning
confidence: 92%
See 2 more Smart Citations
“…Similar studies were conducted by Levy et al (1999) and Aiello et al (2007). Some investigators (Estevez et al 2010) reported less or no effect of soil salinisation due to recycled water application in open spaces. However, to be on the safe side, an intensive management and long term monitoring was recommended to avoid mass loading of salt and nutrients in soil (Tanji 1997;Zhang et al 2006).…”
Section: Soil Healthsupporting
confidence: 64%